Deadly Life in Illyria: Slobodan Novak and the Archives of the Revolution - Jukić, Tatjana (2008)
Published in 1968, Scents, Gold and Incense by Slobodan Novak has remained a focal point against which to define what in the meantime has been taking shape as the « present» of Croatian literature – a positionality it prefigures from within its own focal figure, that of the undying dying Madona Markantunova. From within the figure of the undying death as such and, consequently, from within the warp this specter has formed in the intervening history of Croatian literature, Novak’ s novel seems to invoke, as its spectral future, a reading of spectral futures later conjured in the work of Jacques Derrida, specifically as the act of invocation in both these cases operates from within various ghosts of Shakespeare and Marx. Working with these various phantoms, my analysis of Novak’ s novel aims at outlining a mnemonic fault or fold it projects in both the history of Croatian literature and the temporalities of critical theory.
Projekt MZOS
ENG